Dinamika dan Tantangan Pustakawan di Era Globalisasi - Muhammad Tawwaf (Media Pustakawan, 2017)
Abstract In the various of librarian forums are still intense and interesting to discuss about the competence and professionalism of librarians, its because of the profession of librarians in this era of globalization is a very strategic profession and received a very wide attention among libraries, especially in the library of universities in terms of Information management. Competence and professionalism for those who hold this profession are a challenge and discussed in the various of librarian forums in the global era. Librarian readiness to face the digital era in meeting the needs of users who are very diverse information by the user cannot be considered normal, As information managers, librarians in the era of information flooding in cyberspace today requires competence and professionalism as the librarian definitions contained in Law no. 43 of 2007 on libraries, that librarian is someone who has competence obtained through education and/or training librarianship and has the duty and responsibility to implement library management and services. Librarians are currently dealing with users who are called “native engine” users who are not separated daily with information technology tools that all want fast, easy and efficient in terms of information accessibility. Information packs that will slowly shift from paper to soft sources into librarian bets to understand and be able to manage and distribute various of information in the data base. The third millennium is an information age that forces librarians to begin switching paradigms and repositioning their roles over the years. The independence and productivity of librarians to change and become agents of change for themselves and society, and being able to position themselves as information managers for the community is imperative. The competence of librarians in terms of online research skills should also be held to anticipate the needs of users, especially researchers who are in dire need of various sources that have been packaged in digital form, as the researcher consumption must be obtained from E’Journal and publication also through open journal system or scopus is a challenge for librarians as information manager. One of the aims of this paper is to publicize and reveal what librarians need to anticipate in the era of information flooding in the face of technological developments and the current changing phenomenon, so librarians must be able to uncover what is changing and what should to do. The Demands of the needs of library users increasingly diverse in this information technology era, the library needs to prepare a professional librarian and competent in their fields which, according to some librarian research results have not been encouraging.